Efektifitas model discovery learning dalam meningkatkan kemampuan pemecahan masalah matematika siswa - Dewi, Liana; Rahmawati, Helmi; Solihah, Fatimatus (Universitas Qamarul Huda Badaruddin, 2025)
This study aims to analyze the effectiveness of the discovery learning model in improving students’ mathematical problem-solving skills in Grade VII of SMPN 3 Praya Tengah during the 2024/2025 academic year. The research employed a quasi-experimental method with a pretest-posttest control group design. The sample consisted of 40 students divided into two groups: an experimental class (20 students) applying the discovery learning model, and a control class (20 students) using conventional teaching methods. The research instrument was a problem-solving test on algebra, administered before and after the treatment. Data analysis using an independent samples t-test showed a significant difference between the experimental and control groups with a sig. (2-tailed) = 0.000 < 0.05. This indicates that the discovery learning model is effective in enhancing students’ mathematical problem-solving skills.